Relative Influence of Host, Wolbachia, Geography and Climate on the Genetic Structure of the Sub-saharan Parasitic Wasp Cotesia sesamiae - Branca, Antoine; Le Ru, Bruno; Calatayud, Paul-André; Obonyo, Julius; Musyoka, Boaz; Capdevielle-Dulac, Claire; Kaiser-Arnauld, Laure; Silvain, Jean-François; Gauthier, Jérémy; Paillusson, Corentin; Gayral, Philippe; Herniou, Elisabeth A.; et al. (Frontiers in Ecology and Evolution, 2019)
The parasitoid lifestyle represents one of the most diversified life history strategies on earth. There are however very few studies on the variables associated with intraspecific diversity of parasitoid insects, especially regarding the relationship with spatial, biotic and abiotic ecological factors. Cotesia sesamiae is a Sub-Saharan stenophagous parasitic wasp that parasitizes several African stemborer species with variable developmental success. The different host-specialized populations are infected with different strains of Wolbachia, an endosymbiotic bacterium widespread in arthropods that is known for impacting life history traits, notably reproduction, and consequently species distribution. In this study, first we analyzed the genetic structure of C. sesamiae across Sub-Saharan Africa, using 8 microsatellite markers. We identified five major population clusters across Sub-Saharan Africa, which probably originated in the East African Rift region and expanded throughout Africa in relation to host genus and abiotic factors, such as Köppen-Geiger climate classification. Using laboratory lines, we estimated the incompatibility between the different strains of Wolbachia infecting C. sesamiae. We observed that incompatibility between Wolbachia strains was asymmetric, expressed in one direction only. Based on these results, we assessed the relationships between the direction of gene flow and Wolbachia infections in the genetic clusters. We found that host specialization was more influential on genetic structure than Wolbachia-induced reproductive incompatibility, which in turn was more influential than geography and current climatic conditions. These results are discussed in the context of African biogeography, and co-evolution between Wolbachia, virus parasitoid and host, in the perspective of improving biological control efficiency through a better knowledge of biological control agents’ evolutionary ecology.